2016
DOI: 10.1007/s11306-016-0968-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum fatty acid and lipoprotein subclass concentrations from prepuberty to adulthood and during aging

Abstract: Concentrations in serum were determined for 18 fatty acids (FAs) and 21 lipoprotein main and subclasses by chromatographic analyses and the average size was calculated for very low density (VLDL), low density (LDL) and high density (HDL) particles. 283 ethnic Norwegian children and adults from the rural Fjord region of Western Norway were compared with the objectives to reveal patterns and gender differences during the development from prepuberty to adulthood and during aging in adults. Both genders showed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…
Fig. 1 Principal component (PC) scores before ( a , b ) and after ( c , d ) the median difference correction (Rajalahti et al 2016 ) to reduce systematic analytical differences between the three batches. Five samples from run 1 were reanalyzed in run 2 and 3.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…
Fig. 1 Principal component (PC) scores before ( a , b ) and after ( c , d ) the median difference correction (Rajalahti et al 2016 ) to reduce systematic analytical differences between the three batches. Five samples from run 1 were reanalyzed in run 2 and 3.
…”
Section: Methodsmentioning
confidence: 99%
“…The measurements of the second batch were corrected by adding the median difference between the five replicates for each variable to all samples in batch 2. This procedure, called median difference correction (MDC) (Rajalahti et al 2016 ), was repeated to correct systematic differences between the third and first batch. The merits of the correction was validated in three ways: (i) by doing a PLS-DA on the corrected data and inspect the SR plot (see Supplementary Material 2), (ii) by performing PCA of the replicates after MDC (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajalahti та співавт. [11] показали, що в осіб обох статей абсолютна концентрація ейкозапен таєнової і докозагексаєнової кислот зростає від препубертату до дорослого віку (до 40 років). Серед жінок цей процес з віком триває (концен трація да н их кислот і далі підвищується) та продовжує т ься навіть у похилому віці, тоді як серед чоловіків такої тенденції немає.…”
Section: оригінальні дослідженняunclassified
“…Rajalahti with the co-authors [15] showed that for individuals of both genders, absolute concentrations of EPA and DHA increase beginning from prepubertal age to adulthood (up to 40 years). Among women, this process continues with age (EPA and DHA continues to increase) and continues even in the elder age, while there is no such tendency among men.…”
mentioning
confidence: 96%